Rare Abdominal Wall Metastasis following Curative Resection of Gastric Cancer: What Can Be Learned from the Use of Percutaneous Catheters? - Arthur A. Parsee; Kerry L. Thomas; Masoumeh Ghayouri; Rutika Mehta; Kujtim Latifi; Jennifer Sweeney; Daniel Jeong; Abraham Ahmed (Case Reports in Oncological Medicine)
In cancer care, tissue seeding after curative resections is a known potential complication, despite precautions taken during surgical treatment. We present an uncommon case of an abdominal wall metastasis along the tract of a surgical drain following gastrectomy for gastric adenocarcinoma. To our knowledge, this is the first case of such an occurrence in the setting of a negative staging peritoneal lavage. Aside from the rarity of such a recurrence, this instance highlights an opportunity to reevaluate best practices with regard to the extent of coverage of postoperative salvage radiotherapy. The oncologic patient provides many challenges and may require multiple catheters for drainage and at times infusion of nutrition or therapeutic agents. These foreign bodies should be scrutinized both clinically and radiographically, as they may create vulnerabilities in keeping malignant diseases contained and controlled. We provide a review of the literature with reasonable treatment options for the benefit of future patients.